A super-tough wide temperature range damping elastomer composite material and preparation method thereof
By using tannin acid, calcium chloride and phosphate in polyurethane, combined with supercooled water to induce in situ crystallization at the interface, phosphate crystals are generated, which solves the problems of poor mechanical properties and insufficient damping performance of polyurethane composite materials, and improves ultra-toughness, high strength and wide temperature domain damping performance.
Patent Information
- Application Number
- CN202410932259.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-12
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-07-12
AI Technical Summary
Existing polyurethane composites have problems such as poor mechanical properties, low glass transition temperature and lack of functionality. Especially when using inorganic particles to assist hydrogen bonding to enhance toughening, the interface debonding and glass transition temperature increase are limited.
By introducing tannin acid, calcium chloride and phosphate into polyurethane, and inducing in situ crystallization at the interface using supercooled water, phosphate crystals are generated to improve the mechanical properties and damping properties of the composite material.
The ultra-toughness, high strength, and high elongation of break of polyurethane composite materials are achieved, and the damping temperature range is expanded, significantly improving the mechanical and damping properties of the material.
Smart Images

Figure CN118703051B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of multifunctional composite materials, and in particular to an ultra-tough wide-temperature-range damping elastomer composite material and a preparation method thereof. Background Art
[0002] Due to its own high entropy elastic properties, elastomers are able to dissipate mechanical energy when stretched and deformed, and recover mechanical properties after stress removal. Therefore, they are widely used in aerospace, construction, electronics and other fields. However, with the increasing popularization and deepening of sustainable development and green environmental protection concepts, there is an increasing demand for elastomer composites with self-healing ability and recyclable potential constructed through dynamic non-covalent interactions. In order to meet the above needs, the research and exploration of elastomer composites with dynamic properties has become a hot research direction, among which elastomers constructed by dynamic hydrogen bonds have been widely studied.
[0003] However, as the research progressed, the researchers found that elastomers prepared only by hydrogen bond crosslinking had poor mechanical properties. In order to solve this problem, the researchers introduced inorganic particles into the elastomer to assist hydrogen bond strengthening and toughening. However, due to their interfacial inertness, the directly introduced inorganic particles are prone to interfacial debonding with the matrix, resulting in limited improvement in the mechanical properties of the elastomer. In addition, the glass transition temperature of common elastomer matrices (such as polyurethane) is low, and the direct introduction of inorganic particles does not significantly increase its glass transition temperature, thereby limiting its application. Finally, the direct introduction of inorganic particles into the matrix does not significantly improve the damping properties of the composite material.
[0004] Therefore, there is an urgent need in this field to develop a polyurethane composite material that can produce truly ultra-tough, high-strength, and wide-temperature damping polyurethane composite materials that can fundamentally solve the defects of traditional composite materials prepared by inorganic particle-assisted hydrogen bond reinforcement and toughening. Summary of the invention
[0005] In order to solve the above technical problems, the purpose of the present invention is to provide an ultra-tough wide temperature range damping elastomer composite material and a preparation method thereof, which effectively solves the problems of poor mechanical properties, low glass transition temperature and lack of functionality of existing polyurethane composite materials.
[0006] The technical solution of the present invention to solve the above technical problems is as follows: a method for preparing an ultra-tough wide temperature range damping elastomer composite material is provided, comprising the following steps:
[0007] (1) dissolving tannic acid in deionized water, then adding calcium chloride to dissolve, and freezing to obtain solution ice cubes;
[0008] (2) dissolving disodium hydrogen phosphate dodecahydrate and sodium dihydrogen phosphate in deionized water to obtain a mixed solution;
[0009] (3) adding the solution ice cubes obtained in step (1) and the mixed solution obtained in step (2) to the aqueous polyurethane solution, stirring until the solution ice cubes are completely melted, vacuum filtering and drying to obtain an ultra-tough wide temperature range damping elastomer composite material.
[0010] Furthermore, in step (1), the mass volume ratio of tannic acid, calcium chloride and deionized water is 3-7 g: 3-7 g: 100 mL.
[0011] Furthermore, in step (1), the product is placed in liquid nitrogen for low-temperature freezing.
[0012] Furthermore, in step (1), ultrasound is used to assist tannic acid in dissolving in deionized water.
[0013] Furthermore, in step (2), the mass volume ratio of disodium hydrogen phosphate dodecahydrate, sodium dihydrogen phosphate and deionized water is 1-4 g: 0.5-3 g: 100 mL.
[0014] Furthermore, disodium hydrogen phosphate dodecahydrate can be replaced by dipotassium hydrogen phosphate with crystal water, and sodium dihydrogen phosphate can be replaced by potassium dihydrogen phosphate.
[0015] Furthermore, in step (3), the mass volume ratio of the aqueous polyurethane solution, the mixed solution and the solution ice cubes is 1-3g:35-75mL:35-75mL.
[0016] Furthermore, the solid content of the aqueous polyurethane solution is 20%-70%.
[0017] Furthermore, in step (3), a PP filter membrane with a pore size of 0.22 μm is used for suction filtration.
[0018] Furthermore, in step (3), drying is performed at a temperature of 40-80°C.
[0019] The present invention also provides an ultra-tough wide-temperature-range damping elastomer composite material obtained by the preparation method of the ultra-tough wide-temperature-range damping elastomer composite material.
[0020] The present invention has the following beneficial effects:
[0021] 1. During the preparation of the present invention, the tannic acid coordinated with calcium ions is rapidly frozen under liquid nitrogen (named as cold quenching ice), and then rapidly melted in a mixed solution of disodium hydrogen phosphate dodecahydrate, sodium dihydrogen phosphate and polyurethane. When the cold quenching ice melts, supercooled water is generated at the interface with water in the polyurethane mixed solution. The calcium ions exposed to the supercooled water and the hydrogen phosphate and dihydrogen phosphate in the polyurethane mixed solution are crystallized in a restricted manner within the surface to generate phosphate.
[0022] 2. Water is rapidly frozen (cold quenched ice) in liquid nitrogen and then rapidly melted in the solution to obtain supercooled water, and phosphate crystals are formed on the surface of the supercooled water, thereby increasing the mechanical properties of the composite material. Tannic acid does not react with phosphates, nor is it ball-milled. Instead, it is directly coordinated with calcium ions, so there are no phosphate molecules.
[0023] 3. The present invention obtains an ultra-tough wide-temperature-range damping elastomer composite material by a preparation method of supercooled water-induced interface in-situ crystallization, which can generate phosphate (hydroxyapatite and calcium hydrogen phosphate) in situ in the polyurethane composite material to improve the interface bonding effect between hydroxyapatite and the polymer matrix; the composite material has ultra-toughness (1261MJ·m -3 ), high strength (50.8MPa), high elongation at break (4206%), and a wide damping temperature range (>120℃; temperature range of tanδ>0.3).
[0024] 4. The present invention improves the binding effect between inorganic phosphate particles and the polyurethane matrix through an in-situ crystallization method, increases the density of dynamic bonds in the composite material, avoids the problem of tannic acid agglomeration in the polymer substrate, and effectively solves the problems of poor mechanical properties, low glass transition temperature and lack of functionality of the polyurethane composite material obtained by directly introducing inorganic particles to assist hydrogen bond strengthening and toughening in the prior art.
[0025] 5. The preparation method of the present invention has the advantages of simple process, strong controllability, good stability, mild reaction conditions, low cost, etc. The overall process is conducive to large-scale industrial processing. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 Schematic diagram of the force performance test results of the ultra-tough wide temperature range damping elastomer composite material obtained in Example 1;
[0027] Figure 2 Schematic diagram of the damping performance test results of the ultra-tough wide temperature range damping elastomer composite material obtained in Example 1;
[0028] Figure 3 This is a schematic diagram of the crystal characterization results of the ultra-tough wide temperature range damping elastomer composite material obtained in Example 1;
[0029] Figure 4 This is a schematic diagram of the structural characterization results of the ultra-tough wide temperature range damping elastomer composite material obtained in Example 1. DETAILED DESCRIPTION
[0030] The principles and features of the present invention are described below, and the examples are only used to explain the present invention and are not used to limit the scope of the present invention. If no specific conditions are specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially.
[0031] Example 1
[0032] A super-tough wide temperature range damping elastomer composite material, the preparation method of which comprises the following steps:
[0033] (1) Dissolve 5 g of tannic acid in 100 mL of deionized water, then add 5 g of calcium chloride to dissolve, and place in -80°C liquid nitrogen for low-temperature freezing to obtain solution ice cubes;
[0034] (2) dissolving 3 g of disodium hydrogen phosphate dodecahydrate and 2 g of sodium dihydrogen phosphate in 100 mL of deionized water to obtain a mixed solution;
[0035] (3) Add the solution ice cubes obtained in step (1) and 40 mL of the mixed solution obtained in step (2) to 2 g of an aqueous polyurethane solution with a solid content of 60%, stir until the solution ice cubes are completely melted, vacuum filter, and dry at 70° C. to obtain an ultra-tough wide-temperature range damping elastomer composite material.
[0036] Example 2
[0037] A super-tough wide temperature range damping elastomer composite material, the preparation method of which comprises the following steps:
[0038] (1) Dissolve 3 g of tannic acid in 100 mL of deionized water, then add 3 g of calcium chloride to dissolve, and place in -80°C liquid nitrogen for low-temperature freezing to obtain solution ice cubes;
[0039] (2) dissolving 1 g of dipotassium hydrogen phosphate trihydrate and 0.5 g of potassium dihydrogen phosphate in 100 mL of deionized water to obtain a mixed solution;
[0040] (3) Add the solution ice cubes obtained in step (1) and 30 mL of the mixed solution obtained in step (2) to 1 g of an aqueous polyurethane solution with a solid content of 60%, stir until the solution ice cubes are completely melted, vacuum filter, and dry at 70° C. to obtain an ultra-tough wide-temperature range damping elastomer composite material.
[0041] Example 3
[0042] A super-tough wide temperature range damping elastomer composite material, the preparation method of which comprises the following steps:
[0043] (1) Dissolve 7 g of tannic acid in 100 mL of deionized water, then add 7 g of calcium chloride to dissolve, and place in liquid nitrogen at -80°C for low-temperature freezing to obtain solution ice cubes;
[0044] (2) dissolving 4 g of disodium hydrogen phosphate dodecahydrate and 3 g of sodium dihydrogen phosphate in 100 mL of deionized water to obtain a mixed solution;
[0045] (3) Add the solution ice cubes obtained in step (1) and 60 mL of the mixed solution obtained in step (2) to 3 g of an aqueous polyurethane solution with a solid content of 60%, stir until the solution ice cubes are completely melted, vacuum filter, and dry at 70° C. to obtain an ultra-tough wide-temperature range damping elastomer composite material.
[0046] Comparative Example 1
[0047] A polyurethane composite material is prepared by directly introducing hydroxyapatite into polyurethane according to Alhamoudi et al. (Alhamoudi FH, The role of fabrication methods and the impact of hydroxyapatite content on PU / HA scaffolds for tissue regeneration, Journal of Materials Research 39 (2024) 1011-1022). Due to the limitations of the method, the prepared material has poor interface contact, poor mechanical properties, and poor damping performance.
[0048] Test Example 1: Mechanical Properties
[0049] The ultra-tough wide temperature range damping elastomer composite material obtained in Example 1 was tested, and a pure polyurethane comparative sample was prepared at the same time. The mechanical properties of the samples were tested by a tensile testing machine, and the results are as follows: Figure 1 shown.
[0050] Depend on Figure 1 It can be seen that the ultra-tough wide temperature range damping elastomer composite material obtained by the present invention exhibits high stress, strain and toughness, among which the highest toughness can reach 1261 MJ·m 3 , tensile strength can reach 50.8MPa, elongation at break can reach 4206%, and it has extremely high mechanical properties. The results show that the lamellar phosphate prepared by the supercooled water-assisted in-situ crystallization of the phase interface can significantly improve the mechanical properties of the material.
[0051] Test Example 2: Damping Performance
[0052] The ultra-tough wide temperature range damping elastomer composite material obtained in Example 1 was tested, and a pure polyurethane comparative sample was prepared at the same time. The loss factor tanδ curve of the composite material was tested with a dynamic mechanical analyzer to test the damping performance of the composite material. When tanδ>0.3, the composite material showed that the composite material had damping performance. The results are as follows: Figure 2 shown.
[0053] Depend on Figure 2 It can be seen that the ultra-tough wide temperature range damping elastomer composite material obtained by the present invention exhibits relatively excellent damping performance, the temperature range of the damping performance is greater than 120°C, the softening temperature of the composite material is close to 140°C, and the maximum value of tanδ is also higher than 0.5, but not greater than 0.6.
[0054] Experimental Example 3: Crystal Characterization
[0055] The ultra-tough wide temperature range damping elastomer composite material obtained in Example 1 was tested, and the original sample of the prepared composite material and the sintered powder were subjected to XRD test. The test results were compared with the standard card of crystals in Jade 6. The results are as follows: Figure 3 shown.
[0056] Depend on Figure 3 It can be seen that the ultra-tough wide temperature range damping elastomer composite material obtained by the present invention has good crystallinity, and the prepared composite material contains two crystals of hydroxyapatite and calcium hydrogen phosphate, while the powder after sintering basically contains only one crystal of hydroxyapatite. It is proved that the preparation method of supercooled water-assisted phase interface in-situ crystallization can effectively prepare hydroxyapatite crystals.
[0057] Experimental Example 4: Structural Characterization
[0058] The ultra-tough wide temperature range damping elastomer composite material obtained in Example 1 was tested, and the original sample of the prepared composite material and the sintered powder were tested by Fourier infrared spectroscopy. The results are as follows: Figure 4 shown.
[0059] Depend on Figure 4 It can be seen that the ultra-tough wide temperature range damping elastomer composite material obtained by the present invention has characteristic absorption peaks of TA and phosphate, and the infrared of the sample after sintering in the prepared composite material matches the infrared characteristic peak of hydroxyapatite, which further proves that the preparation method of in situ crystallization at the phase interface assisted by supercooled water can effectively prepare hydroxyapatite crystals.
[0060] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing an ultra-tough wide temperature range damping elastomer composite material, characterized in that: The following steps are involved: (1) Dissolve tannic acid in deionized water, then add calcium chloride to dissolve, and freeze to obtain solution ice cubes; the mass volume ratio of tannic acid, calcium chloride and deionized water is 3-7 g: 3-7 g: 100 mL; (2) dissolving disodium hydrogen phosphate dodecahydrate and sodium dihydrogen phosphate in deionized water to obtain a mixed solution; the mass volume ratio of disodium hydrogen phosphate dodecahydrate, sodium dihydrogen phosphate and deionized water is 1-4 g:0.5-3 g:100 mL; (3) Adding the solution ice cubes obtained in step (1) and the mixed solution obtained in step (2) to the aqueous polyurethane solution, stirring until the solution ice cubes are completely melted, vacuum filtering and drying to obtain an ultra-tough wide temperature range damping elastomer composite material; the mass volume ratio of the aqueous polyurethane solution, the mixed solution and the solution ice cubes is 1-3 g: 35-75 mL: 35-75 mL.
2. The method for preparing the ultra-tough wide temperature range damping elastomer composite material according to claim 1, characterized in that: In step (1), the sample is placed in liquid nitrogen for low-temperature freezing.
3. The method for preparing the ultra-tough wide temperature range damping elastomer composite material according to claim 1, characterized in that: In step (1), tannic acid is dissolved in deionized water with the aid of ultrasound.
4. The method for preparing the ultra-tough wide temperature range damping elastomer composite material according to claim 1, characterized in that: In step (3), filtration is performed using a PP filter membrane with a pore size of 0.22 μm.
5. The method for preparing the ultra-tough wide temperature range damping elastomer composite material according to claim 1, characterized in that: In step (3), drying is performed at a temperature of 40-80°C.
6. The super-tough wide temperature range damping elastomer composite material obtained by the preparation method of the super-tough wide temperature range damping elastomer composite material according to any one of claims 1 to 5.
Citation Information
Patent Citations
Controlled release, biodegradable core-shell microcapsule compositions
EP3952648A1
Lignocellulosic bioplastics and composites, and methods for forming and use thereof
EP4214246A1